Chagasic megacolon - Machaín Vega, Gustavo; Vanuno, David; Kasamatsu, Elena; Nunes, María Del Carmen; Almirón, María; Russomando, Graciela (Cirugía del Uruguay, 1997)
Chagas's disease caused by Trypanosoma cruzy, a parasite that is transmitted to humans by the hematophagic triatominae insects, is a endemic clinical entity.